LC-MS/MS METHOD FOR L-DOPA QUANTIFICATION IN DIFFERENT TISSUES OF Vicia faba - Jessy Pavón-Pérez; Claudia Oviedo; Mhartyn Elso-Freudenberg; Karem Henriquez-Aedo; Mario Aranda (Journal of the Chilean Chemical Society, 2019)
A rapid, sensitive, precise and accurate liquid chromatography tandem mass spectrometry (LC-MS/MS) method was developed for levo 3,4-dihydroxyphenylalanine (L-DOPA) determination in Vicia faba during different growth stages. The method applied a simple sample preparation step followed by a chromatographic separation on a Kinetex XB Core-Shell C18 (100 mm x 4.6 mm, 2.6 µm) column, using a mixture of ultrapure pure water (A) with 0.5 % (v/v) formic acid and methanol (B) as mobile phase. Analysis of L-DOPA was carried out by MS/MS applying a Multiple Reaction Monitoring (MRM) method using the transition m/z 198 → m/z 152. This LC-MS/MS method allowed a well-resolved detection of L-DOPA in ca. 2 min within 6 min run. Method was validated showing a linear range from 0.05 to 10 mg L-1 (R2 = 0.99); repeatability showed RSD value of 1.40%. Recoveries ranged from 94.14 to 116.62% with RSD values ≤ 5.66% and detection and quantification limits were 0.01 and 0.05 mg L-1, respectively. Applying this validated method, L-DOPA was determined in Vicia faba samples to determined its tissue distribution. As expected, a broad range of L-DOPA content finding values from 4.72 (in seeds) up to 133.60 mg g-1 (sprouts).